The Tellian Units, the Sellaoua Window and the High Medjerda Foreland in the Souk Ahras Area, NE Algeria - Abdallah CHABBI; Chermiti Asma; Brusset Stéphane; Chouabbi Abdelmadjid; Benyoussef Mohamed (My University, 2023)
In northeastern Algeria and south of Annaba city, the Souk Ahras region forms the southern Tellian external domain. It exhibits a complex structure characterized by the stacking of Tellian thrust sheets. These units are thrust above the Sellaoua and High Medjerda foreland and are overthrust by the Numidian thrust sheet. The overall structure is complicated by the presence of Triassic evaporitic bodies, which occur in various positions in the stratigraphic pile. Several tectonic phases have deformed this area in the Cenozoic. In this work, we have updated the stratigraphy and integrated it with geometric, structural, and tectonic surface data to characterize the structural style of the Tellian thrust sheets and their relationship with the surrounding units. The Paleocene to Eocene of the Tellian thrust sheets encompasses two main facies: deep marine globigerina facies to the north (Ouled Driss Sector), and shallow marine nummulitid facies to the south (Boukebch and Dekma areas), both have been unconformably covered by the Miocene. The Tellian thrust sheets of the Souk Ahras region exhibit a duplex geometry in the northern sector and an imbricate fan of thrusts to the south. These units are thrust over the Sellaoua and High Medjerda parautochthonous foreland with a basal decollement in the Paleocene series. The tectonics wedge involves also the Sellaoua and High Medjerda foreland strata, leading to a classic fold-and-thrust belt structure.